Daya Tarik Dompet Digital - Puji Rahayuningsih; Susanto Susanto (Jurnal Riset Manajemen dan Bisnis, 2021)
This research was conducted on the Ovo digital wallet which aims to find out what is the attraction of Ovo, so people use Ovo more than other digital wallets in payment transactions. This study uses a qualitative method, by using triangulation of data sources namely observation, interviews and documentation. Informants in this study are people who have knowledge in the topic under study. And data analysis used with analysis techniques in the form of data reduction, data presentation and drawing conclusions. The results of this study indicate that in the midst of a lot of competition at this time Ovo is intensively conducting sales promotions in the form of cashback and vouchers, so consumers feel they benefit more by using Ovo as their payment instrument compared to other digital wallets. Ovo is superior because it has an easy to fill balance feature without additional administrative costs that are not owned by other digital wallets. In addition, the attraction of Ovo is because in Ovo there is a transfer feature to the bank without additional administrative costs. This is a favorite feature of Ovo users themselves. At present hundreds of merchants have become Ovo's partners. Ovo offers convenience in its features so that it makes consumers feel easier in carrying out activities. More practical, fast and easy transactions, Ovo's presence provides benefits such as shortening their payment time, no need to carry or save large amounts of cash.